PENGARUH LANGSUNG DAN TIDAK LANSGUNG KARAKTERISTIK KOMITE AUDIT TERHADAP LUAS PENGUNGKAPAN CSR MELALUI MANAJEMEN RISIKO - Prasetiyani, Paramita; Ghozali, Imam (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2022)
This study aims to examine the effect of audit committee characteristics on CSRD in manufacturing and mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2019. In addition, this study also examines whether there is an effect of risk management as a mediating variable in the relationship between audit committee characteristics and CSR disclosure. This research using purposive sampling method, which result in 178 samples. The analytical tool in this research using structural equation modeling (SEM)-PLS (Partial Least Square). The results show that the characteristics of the independent audit committee, number of member meetings, financial expertise and gender diversity have a positive effect on CSRD, while the size of the audit committee has no effect on CSRD. Indirect testing shows that risk management only affects the relationship between the number of member meetings and CSRD. Meanwhile, risk management failed to become a mediator for other variables with CSRD.